APLICATION OF RAPID TEST CONTROL FOR PREVENTION PNEUMONIA IN CHILDREN - Nilwan Andiraja; Adly Saddam Khadafi; Muhammad Firdaus; Vania Anjani; Dini Sahrani (Math Educa Journal, 2025)
Pneumonia is a disease which is having similar symptoms like ISPA. It is probably that making many parents did not realize if their children severe Pneumonia. Because according to Indonesia ministry health, there was significant increasingly Pneumonia cases year by year from 2021 to 2024, in 2024 is a year with highest Pneumonia cases, almost 800.000 Pneumonia cases even BPJS report, budget for Pneumonia therapy is highest than other diseases. Then, we need to make a quick preventative action, one of them is optimal control with rapid test. Rapid test is needed in order to detect an individual severe Pneumonia. In order, the aim will success so we need to develop SEIR model with add a control of rapid test to the exposed class. The addition is needed because children have symptom acquiring a certainty Pneumonia infected or not so the therapy will be quick and correct. After that, we need to find the optimal control of rapid test and then to describe the effect of optimal control on the exposed, infected, and recovered classes. The parameters values need to input to the equations which was given a control and next, we have to calculate with used sweep method step forward-backward and with helped by MATLAB software obtain the final result. The result is with control the number individual infected Pneumonia decreasing since initial time till 100th days, meanwhile without control the number individual infected increase till 10th days and after that the plot becomes decrease till 40th days.